1976
DOI: 10.1159/000180593
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Intrarenal Blood Flow after Renal Denervation in the Dog

Abstract: The effect of acute denervation of the kidney on renal sodium and water excretion, and hemodynamics including intrarenal blood flow, was studied in anesthetized dogs. The intrarenal blood flow was measured by the radioactive microsphere method. In all experiments denervation natriuresis and diuresis were observed without significant change in glomerular filtration rate, renal blood flow and distribution of intrarenal blood flow. There was, however, an associated increase in potassium excretion. We suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…Middle and outer cortical flows, however, were not statistically different, indicating that any redistribution of flow away from the deep cortex secondary to denervation was minimal. This corroborates the conclusions of others on anaesthetised (Nomura et al 1976;Bonjour et al 1969) as well as unanaesthetized (Pomeranz et al 1968; Klisiecki, Pickford, Rothschild & Verney, 1931) preparations, that adrenergic influences on cortical flow during resting conditions are small, if any.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Middle and outer cortical flows, however, were not statistically different, indicating that any redistribution of flow away from the deep cortex secondary to denervation was minimal. This corroborates the conclusions of others on anaesthetised (Nomura et al 1976;Bonjour et al 1969) as well as unanaesthetized (Pomeranz et al 1968; Klisiecki, Pickford, Rothschild & Verney, 1931) preparations, that adrenergic influences on cortical flow during resting conditions are small, if any.…”
Section: Discussionsupporting
confidence: 91%
“…The controversy is unresolved by denervation studies. Some authors (Nomura, Kibe, Arai, Uno & Takeuchi, 1976;Bonjour, Churchill and Malvin, (1969) failed to demonstrate a change in renal blood flow after denervation although others have reported redistribution towards the deep cortex (Benscath, Szalay & Takacks, 1971) as also the outer cortex (Lackner & McKay, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…However, the systemic blood pressure was not affected by the renal denervation. Previous studies also showed that the denervation diuresis occurred without significant changes in glomerular filtration rate, renal blood flow and distribution of intrarenal blood flow [12, 13]. It is unlikely that the decreased expression of AQP channels in the denervated kidney should be attributed to altered local hemodynamics.…”
Section: Discussionmentioning
confidence: 90%
“…2 and 3). Interruption of the spontaneous activity by denervation of the kidney has been found in most investigations to result in a diuresis and natriuresis, without any detectable alterations in renal blood flow or glomerular filtration rate (Takics et al 1971, Bencsath et al 1972, Bello-Reuss et al 1975Nomura et al 1976, DiBona & Rios 1980. Comparable results have been obtained on stimulation of the renal nerves at a low level, i.e.…”
Section: Biological Considerationsmentioning
confidence: 98%
“…As the normal spontaneous activity of the renal nerves is 1-2 Hz (Kendrick et al (1972) and Thoren outer zone & Riksten (1979)), the nerves would control the urinary output via the regulation of tubular fluid reabsorption. Consequently, denervation of the kidney should induce a diuresis and natriuresis owing to the effects on the tubular epithelial cells and not due to any haemodynamic changes (Takhcs et al 1971, Bencshth et al 1972, Bello-Reuss et al 1975, Nomura et al 1976, DiBona & Rios 1980. In a previous study from this laboratory (Hermansson 1981) we suggested that even a low level of stimulation will be accompanied by a vasoconstriction.…”
mentioning
confidence: 92%